Novel protein and poxvirus-based vaccine combinations for simultaneous induction of humoral and cell-mediated immunity. - Hutchings, C; Gilbert, S; Hill, A; Moore, A (2005)
The presence of both cell-mediated and humoral immunity is important in protection from and clearance of a number of infectious pathogens. We describe novel vaccine regimens using combinations of plasmid DNA, poxvirus and protein to induce strong Ag-specific T cell and Ab responses simultaneously in a murine model. Intramuscular (i.m.) immunization with plasmid DNA encoding the middle Ag of hepatitis B (DNA) concurrently with a commercial hepatitis B virus (HBV) vaccine (Engerix-B) followed by boosting immunizations with both modified vaccinia virus Ankara (MVA) encoding the middle Ag of HBV and Engerix-B induced high levels of CD4(+) and CD8(+) T cells and high titer Ab responses to hepatitis B surface Ag (HbsAg). Substitution of Engerix-B with adjuvant-free rHBsAg induced similar T cell responses and greatly enhanced Ab levels. Repeated immunizations with recombinant or nonrecombinant MVA mixed with Ag induced higher titers of Abs compared with immunization with either Ag or Engerix-B further demonstrating this novel adjuvant effect of MVA. The poxviruses NYVAC, fowlpox (FP9) and ALVAC, and to a lesser extent, adenovirus, also displayed similar adjuvant properties when used in combination with rHBsAg. The use of poxviruses as an adjuvant for protein to concurrently induce Ag-specific T cells and Abs could be applied to the development of vaccines for many diseases, including HIV and malaria, where both cell mediated and humoral immunity may be important for protection.